Green Accounting, Profitability, Risk Minimization, and Slack Resources in Enhancing CSR Disclosure Quality : An Economic Perspective - Majidah, Majidah; Zahra, Pasha Aulia Lutfia (International Journal of Economics Development Research (IJEDR), 2025)
This study examines the contribution of green accounting, profitability, risk minimisation, and slack resources to the quality of corporate social responsibility (CSR) disclosures in raw goods sector companies listed on the Indonesia Stock Exchange (IDX) for 2019-2021. A sample of 15 companies or 45 observation data was obtained through purposive sampling. Descriptive statistical analysis methods and panel data regression with random effect models are processed using E-Views 12 software. The findings of this study are that the average quality of CSR disclosure in the raw goods sector industry listed on the IDX is 29.8%. The quality of disclosure is still relatively low. It is dominated by disclosure of economic topics, with most of the disclosure quality being at levels 1 and 2, namely the quality of brief disclosure to quantitative disclosure. The research findings also show that green accounting, risk minimisation, and slack contribute positively to the quality of CSR disclosures. Future researchers can explore other factors contributing to CSR disclosure quality, such as industry type and environmental performance.